2017
DOI: 10.1111/ppl.12607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of rice arsenic‐induced RING finger E3 ligase 2 (OsAIR2) and its heterogeneous overexpression in Arabidopsis thaliana

Abstract: Arsenic (As) accumulation adversely affects the growth and productivity of plants and poses a serious threat to human health and food security. In this study, we identified one As-responsive Really Interesting New Gene (RING) E3 ubiquitin ligase gene from rice root tissues during As stress. We named it Oryza sativa As-Induced RING E3 ligase 2 (OsAIR2). Expression of OsAIR2 was induced under various abiotic stress conditions, including heat, salt, drought and As exposure. Results of an in vitro ubiquitination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Consistent with these studies, we found that overexpression of a RING E3 ligase gene, SlRING1 , in tomato remarkably improved Cd tolerance, suggesting that SlRING1 regulates plant adaptation mechanism to heavy metal stress. Notably, the SlRING1 contained a RING domain and the in vitro ubiquitination assay revealed that SlRING1 had E3 ligase activity (Figure 1), which is consistent with previous results (Hwang et al, 2017). Moreover, the expression of SlRING1 significantly increased in tomato roots under Cd stress (Qi et al, 2020), suggesting its potential involvement in metal uptake and accumulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with these studies, we found that overexpression of a RING E3 ligase gene, SlRING1 , in tomato remarkably improved Cd tolerance, suggesting that SlRING1 regulates plant adaptation mechanism to heavy metal stress. Notably, the SlRING1 contained a RING domain and the in vitro ubiquitination assay revealed that SlRING1 had E3 ligase activity (Figure 1), which is consistent with previous results (Hwang et al, 2017). Moreover, the expression of SlRING1 significantly increased in tomato roots under Cd stress (Qi et al, 2020), suggesting its potential involvement in metal uptake and accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…To cope with heavy metal stress, plants utilize multiple mechanisms, such as reduced metal uptake, chelation of toxic metal ions, and antioxidant accumulation to detoxify ROS (Viehweger, 2014). Moreover, phytochelatins‐dependent detoxification of toxic metal ions and subsequent sequestration of PCs‐metal complexes in vacuoles play a vital role in plant survival under Cd stress (Hwang et al, 2017). Post‐translational protein modifications, particularly UPS‐mediated protein degradation, participate in the responses of plants to environmental stressors, including heavy metals (Liu et al, 2020; Sadanandom et al, 2012; Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…26S proteasome-mediated ubiquitin-dependent protein degradation is known to be an effective response to environmental stress (Smalle et al, 2003;Kurepa et al, 2008). Previously, we demonstrated the roles of several RING E3 ligases in perception and transduction under various abiotic stress conditions through ubiquitin-mediated protein degradation (Lim et al, 2014Park et al, 2015;Hwang et al, 2017). In this study, we confirmed that OsCRF1, composed of 629 amino acids with HC-type RING domain, possesses E3 ligase activity via in vitro ubiquitination assay.…”
Section: Discussionsupporting
confidence: 79%
“…The clone was also expressed in E. coli strain BL21 (Promega) and purified by Ni-NTA Purification System (Invitrogen Life Technologies, Carlsbad, CA). In vitro ubiquitination assay was carried out according to Hwang et al (2017) with some modifications. Each purified MBP-OsCRP1-RD (300 ng) or non-recombinant MBP (negative control) was mixed with 50 ng yeast E1 (Boston Biochemicals, Cambridge, MA, USA), 250 ng of purified AtUBC10 (E2), 10 mg bovine Ub (Sigma-Aldrich, St. Louis, MO, USA), along with 20X reaction buffer (1 M Tris, pH 7.5; 40 mM ATP; 100 mM MgCl 2 ; and 40 mM DTT).…”
Section: Gene Expression Studymentioning
confidence: 99%
“…Multiple reports have shown that several regulators of the PSR, including PHR1 interactors and WRKY6, are subjected to posttranslational modifications such as sumoylation of PHR1 (Miura et al, 2005) or ubiquitination of SPX proteins and Pi transporters (Bayle et al, 2011;Lv et al, 2014;Puga et al, 2017;Yang et al, 2018;Hu et al, 2019;Medici et al, 2019;Ruan et al, 2019;reviewed in Pan et al, 2019). In relation to As(V), components of the 26S proteasome complex in rice and Arabidopsis are involved in the degradation of arsenic transporters (Lim et al, 2014), the regulation of genes involved in phytochelatin biosynthesis (Sung et al, 2009), and enhanced growth in the presence of arsenic (Hwang et al, 2016(Hwang et al, , 2017. However, the role of ubiquitination in the arsenic response remains mostly unknown.…”
Section: Discussionmentioning
confidence: 99%